2009
DOI: 10.1080/00480169.2009.36863
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive safety of an amino-acetonitrile derivative (AAD), monepantel, in rams following repeated oral administration

Abstract: Repeated oral administration of monepantel at three times the MRD every 5 days over an entire spermatogenic cycle and during mating was not associated with any treatment-related adverse effects on the reproductive performance of rams and was systemically very well tolerated. This study demonstrated that this population of rams could tolerate accidental overdoses of up to three times the MRD of monepantel or prolonged repetitive administration at overdoses. Thus, those so treated entering a breeding programme w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…Hennessy and Prichard (1979) suggested that the deaths of cattle administered high volumes of the benzimidazole drug thiabendazole could have occurred after rumen bypass directed lethal concentrations of the drug to the abomasum. Similar results were not experienced either in this study or in ovine target animal safety studies conducted with monepantel, in which recently weaned lambs received eight doses of up to five times the recommended maximum dose at three‐weekly intervals (Malikides and others 2009b), or in adult male and female sheep treated every five days at three times the recommended dose over full reproductive cycles (Malikides and others 2009a, c).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Hennessy and Prichard (1979) suggested that the deaths of cattle administered high volumes of the benzimidazole drug thiabendazole could have occurred after rumen bypass directed lethal concentrations of the drug to the abomasum. Similar results were not experienced either in this study or in ovine target animal safety studies conducted with monepantel, in which recently weaned lambs received eight doses of up to five times the recommended maximum dose at three‐weekly intervals (Malikides and others 2009b), or in adult male and female sheep treated every five days at three times the recommended dose over full reproductive cycles (Malikides and others 2009a, c).…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were not experienced either in this study or in ovine target animal safety studies conducted with monepantel, in which recently weaned lambs received eight doses of up to five times the recommended maximum dose at three-weekly intervals (Malikides and others 2009b), or in adult male and female sheep treated every five days at three times the recommended dose over full reproductive cycles (Malikides and others 2009a, c). …”
Section: Discussionsupporting
confidence: 83%